2018
DOI: 10.1093/heapro/day056
|View full text |Cite
|
Sign up to set email alerts
|

Potential of social media in promoting mental health in adolescents

Abstract: The growing prevalence of adolescent mental disorders poses significant challenges for education and healthcare systems globally. Providers are therefore keen to identify effective ways of promoting positive mental health. This aim of this qualitative study was to explore perceptions that social media might be leveraged for the purposes of mental health promotion amongst adolescents aged between 11 and 18 years. Utilizing focus groups conducted with adolescents (N = 54), educational professionals (N = 16) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 38 publications
6
75
0
4
Order By: Relevance
“…Social media is a potentially accessible, inexpensive way to have conversations about mental health, including to promote healthseeking and reduce isolation. 281 Online friends can be an important source of social support for LGBT, queer or questioning, and intersex youth, and a growing amount of literature suggests that the internet can be a safe haven for some young people belonging to sexual minorities. 282 For families of children with disabilities and illnesses like cerebral palsy, social media can provide a platform for emotional support and forming connections, sharing information and advice, and learning about services, 283 but the quality of information is variable.…”
Section: Children Are Enormously Exposed To Harmful Commercial Marketingmentioning
confidence: 99%
“…Social media is a potentially accessible, inexpensive way to have conversations about mental health, including to promote healthseeking and reduce isolation. 281 Online friends can be an important source of social support for LGBT, queer or questioning, and intersex youth, and a growing amount of literature suggests that the internet can be a safe haven for some young people belonging to sexual minorities. 282 For families of children with disabilities and illnesses like cerebral palsy, social media can provide a platform for emotional support and forming connections, sharing information and advice, and learning about services, 283 but the quality of information is variable.…”
Section: Children Are Enormously Exposed To Harmful Commercial Marketingmentioning
confidence: 99%
“…Of the 16 selected research papers, there were a research focus on adults, gender, and preadolescents [10][11][12][13][14][15][16][17][18][19]. In the design, there were qualitative and quantitative studies [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…Another study revealed that depression and time spent on Facebook by adolescents are positively correlated [22]. More importantly, symptoms of major depression have been found among the individuals who spent most of their time in online activities and performing image management on social networking sites [14].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the pandemic context, and applicable to other issues, this is important to reduce the spread of misinformation ( 34 ). The changing role of social media in health promotion and its increasing usability is being recognized and applied, especially when delivering health promotion messages to large geographic areas when in-person initiatives are not feasible or possible ( 35 , 36 ). As health promoters continue to utilize social media for its advantageous qualities, such as the opportunity for widespread message dissemination in a short time period, more scholarly attention is needed to examine the drawbacks of such approaches.…”
Section: Discussionmentioning
confidence: 99%